Pendidikan Islam dan Pluralisme Beragama - m slamet yahya (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2015)
Islam is a religion that has prophetic mission, namely rahmatan lil â€˜alamin, blessing to universe. To realize this mission, Islamic education must able to produce outputs that have inclusive character, pluralist, and appreciative to pluralism. Pluralism in Islam not only normatively supported by religious texts, but also on praxis-empiric level. Islam also has practiced life orientation that reflected religious plurality. Therefore, on global scale, acknowledgment to religious plurality became essential and significant matter. To realize this, itâ€™s urgently needed wisdom to suppress emotional and radical attitude on everyday life.Â